2022
DOI: 10.3390/ijms232214274
|View full text |Cite
|
Sign up to set email alerts
|

The FKBP51 Inhibitor SAFit2 Restores the Pain-Relieving C16 Dihydroceramide after Nerve Injury

Abstract: Neuropathic pain is a pathological pain state with a broad symptom scope that affects patients after nerve injuries, but it can also arise after infections or exposure to toxic substances. Current treatment possibilities are still limited because of the low efficacy and severe adverse effects of available therapeutics, highlighting an emerging need for novel analgesics and for a detailed understanding of the pathophysiological alterations in the onset and maintenance of neuropathic pain. Here, we show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…SAFit2 is a promising pharmacological agent that inhibits FKBP5 and modulates stress responses [36][37][38]. This small molecule selectively targets FKBP5 but not the closely related FKBP4 [13,39]. Using an animal model of senile osteoporosis, we showed that administration of SAFit2 enhanced bone density.…”
Section: Discussionmentioning
confidence: 99%
“…SAFit2 is a promising pharmacological agent that inhibits FKBP5 and modulates stress responses [36][37][38]. This small molecule selectively targets FKBP5 but not the closely related FKBP4 [13,39]. Using an animal model of senile osteoporosis, we showed that administration of SAFit2 enhanced bone density.…”
Section: Discussionmentioning
confidence: 99%
“…The tissue samples were grinded for 30 to 60 s, with short breaks included to avoid overheating, in an ethanol:water (1:9, v/v) solution, using 119 µl ethanol for DRG samples and 1190 µl ethanol for spinal cord samples. Afterwards, lipid extraction and chromatographic separation was performed as well as the measurement settings and internal standards chosen as previously described [ 24 ]. Instrumental setup consisted of a Vanquish Horizon coupled to an Exploris 480 (both Thermo Fisher Scientific) with Zorbax RRHD Eclipse Plus C8 column (2.1 × 50 mm, 1.8 µm, Agilent) and a pre-column of the same type.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the levels of C16 dihydroceramide (d18:0/ 16:0), an antihyperalgesic lipid mediator, were restored upon treatment with SAFit2 in the lumbar DRG. 71 Overall, the collective studies with SAFit, together with results from FKBP51-deficient mice, suggest inhibition of FKBP51 with the current gold standard SAFit2 as a novel therapeutic strategy for treating chronic pain states.…”
Section: Proof Of Concept: Pharmacological Modulation Of Fkbp51 With ...mentioning
confidence: 98%
“…administration of SAFit2 at the dose of 10 mg/kg impacts on the levels of lipids and lipid-oxidizing enzymes in the DRG and in the SC. In particular, the levels of C16 dihydroceramide (d18:0/16:0), an antihyperalgesic lipid mediator, were restored upon treatment with SAFit2 in the lumbar DRG …”
Section: Proof Of Concept: Pharmacological Modulation Of Fkbp51 With ...mentioning
confidence: 99%
See 1 more Smart Citation